Developmental and activity-dependent modulation of coupling distance between release site and Ca2+ channel - Midorikawa, Mitsuharu (Frontiers in Cellular Neuroscience, 2022)
Synapses are junctions between a presynaptic neuron and a postsynaptic cell specialized for fast and precise information transfer. The presynaptic terminal secretes neurotransmitters via exocytosis of synaptic vesicles. Exocytosis is a tightly regulated reaction that occurs within a millisecond of the arrival of an action potential. One crucial parameter in determining the characteristics of the transmitter release kinetics is the coupling distance between the release site and the Ca2+ channel. Still, the technical limitations have hindered detailed analysis from addressing how the coupling distance is regulated depending on the development or activity of the synapse. However, recent technical advances in electrophysiology and imaging are unveiling their different configurations in different conditions. Here, I will summarize developmental- and activity-dependent changes in the coupling distances revealed by recent studies.